Implementasi Sistem Panic Button Terintegrasi Aplikasi Kawal Desa Dan Sirene Untuk Peningkatan Keamanan Desa Pangauban - Dini Destiani Siti Fatimah; Kamila Lutfi Zakiah; Muhammad Nadhief Rahmat Firdaus; Ihsan Yafi Pirmansyah; Moch. Rifal Azril; Wilyandi Fajri; Kamilaeni; Fadilah Nur Fatimah; Destian Muhammad Lutfi; M. Fikri Akmaludin; Dzikra Ilham Ilahi; Meitha Amanda; Muhammad Fakhri Asy-syauqi; Ghiffari; Rafly Achmad Fauzan; Ray Faizi Muhammad Sumarno; Inayatul Ikrimah; Muhammad Naufal Abdul Tsany; Ipan Munigar Rohman; Muhamad Farhan (Institut Teknologi Garut, 2026)
The village of Pangauban in Cisurupan Subdistrict, Garut Regency, has experienced rapid progress. However, this village does not yet have an adequate integrated security system. This condition has resulted in ineffective communication between village officials and residents when dealing with emergency situations, causing a slow response to reports of important incidents. Therefore, technology-based innovations are urgently needed to facilitate coordination and accelerate response times, thereby enhancing the sense of security for the entire village community. Through the Thematic Community Service Program (KKN), we implemented a Panic Button/Emergency feature on the existing Kawal Desa application. This feature is designed to make it easier for residents to report important incidents, enabling village officials to respond quickly and efficiently. The methods used are quantitative and workshops. The stages of the activity include observation, socialization, and system implementation. The siren hardware is installed in the village office and then configured wirelessly with the Kawal Desa application. After that, socialization and training are provided to RT, RW, and residents on how to use the system, both manually and through the application.